In Vivo Confocal Microscopy Findings in Corneal Stromal Dystrophies - Süleyman Okudan; Emine Tınkır Kayıtmazbatır; Ayşe Bozkurt Oflaz; Banu Bozkurt (Diagnostics)
Background/Objectives: In this study, we aim to evaluate in vivo confocal microscopy (IVCM) findings of corneal stromal dystrophies (CSDs) including granular, macular and lattice corneal dystrophy that can be used for differential diagnosis and monitoring recurrences after surgical interventions. Methods: Patients diagnosed with CSD who were followed-up in the cornea and ocular surface unit were included in this study. IVCM was performed using the Heidelberg Retina Tomograph 3, Rostock Cornea Module (Heidelberg Engineering, Germany) and anterior segment optical coherence tomography (AS-OCT) imaging was performed using the Spectralis OCT (Heidelberg Engineering, Germany). The morphological structure, size and location of deposits, epithelial involvement and presence of inflammatory and dentritic cells were compared among the three stromal dystrophies. Results: A total of 72 eyes from 36 participants were included in this study. Twelve patients (33.33%) had granular corneal dystrophy (GCD), ten (27.77%) had macular corneal dystrophy (MCD) and fourteen (38.88%) had lattice corneal dystrophy (LCD). In GCD, highly reflective deposits varying in size (20 µm–300 µm) were observed. In MCD, diffuse hyperreflective stroma with dark striae, dentritic cells around deposits and abnormal keratocytes were observed. In LCD, there were branching, lattice-like and granular deposits with epithelial cell disruption in some of the eyes. In MCD, the central corneal thickness was thinner (449.44 ± 65.45 µm) compared to GCD and LCD (565.16 ± 49.62 µm and 569.91 ± 39.32 µm p < 0.001). Recurrence was observed in five patients following penetrating keratoplasty. Conclusions: IVCM is a valuable tool for distinguishing CSD subtypes and monitoring recurrence following surgical interventions.